Effect of statin therapy on the prevention of new-onset acute coronary syndrome in patients with rheumatoid arthritis. (15th February 2018) - Huang, Chen-Yu; Lin, Ting-Tse; Yang, Yao-Hsu; Lin, Lian-Yu; Tsai, Chia-Ti; Hwang, Juey-Jen; Chen, Pau-Chung; Lin, Jiunn-Lee
Abstract: Background: The aim of this study is to investigate whether statin therapy can reduce new-onset acute coronary syndrome (ACS) in patients with rheumatoid arthritis (RA). Methods: We used a database from the Registry for Catastrophic Illness from the National Health Research Institute (NHRI) in Taiwan. All RA patients aged 18 or older, diagnosed between 1995 and 2013, without previous cardiovascular events were included. We divided participants into quartiles according to the accumulated statin equivalent dosage and tertiles of period of days of statin treatment to examine the possible dose–response effect. To avoid confounding effects, a 1:4 propensity score matching and Cox's proportional hazard regression models were applied to estimate the hazard ratios for ACS events in patients with and without statin use. Results: Total 49, 227 patients were included and PS matching identified 5483 patients receiving statins and 21, 932 who did not. RA patients treated with statins had lower incidence of first ACS event (IRR 0.779, 95% CI: 0.654–0.927, p = 0.005) after PS matching. Statin therapy is associated with reduced risk of new ACS before PS matching (HR = 0.847, 95% CI: 0.737–0.973, p = 0.019) and the beneficial effect is correlated with accumulated dose and therapy duration (HRs from Q1 to Q4 are 1.215, 0.825, 0.716 and 0.611, p < 0.001 for trend; HRs from T1 to T3 are 1.100, 0.841 and 0.611, p < 0.001 for trend). These results remained robust after propensity matching. Comparison between 6 different statins, rosuvastatin seems to be associated with better outcome on ACS primary prevention after excluding participants taking more than one kind of statin. Conclusions: Our study demonstrated that statin therapy is associated with lower event rate of new-onset ACS in RA patients and the beneficial effect is dose-responsive.